Karnataka Annual Plan 1980-81 Volume-I Review of Planning and Proposals for the Annual Plan - Planning Commission (Planning Commission, 1980)
Karnataka's economy has registered one of the highest growth rates in the country and in recent years, an annual growth rate of around 6 per cent has been maintained. Such a growth has further strengthened agricultural, industrial, infrastructural and institutional base in the state. With a stronger base which the state now possesses and with still unexploited and under-utilised material and human resources, the state is launching a more optimistic programme of development in the new five year plan 1978-83 keeping in view not only the immediate goals and problems, but also a long-run perspective.
Planning Department, Government of Karnataka